Odpowiedzi

2010-03-24T16:39:12+01:00
1/4z+z-6=2/3z-4/3
1/4z+z-2/3z=-4/3+6
3/12z+12/12z=18/12z=-4/3+18/3
7/12z=14/3
7z=56
z=8
1 5 1
2010-03-24T16:42:23+01:00
1/4z+(z-6)=2/3(z-2)
1/4z + z -6 = 2/3z - 1 1/3 (minus jeden i jedna trzecia)
1/4z - 2/3z+ z= - 1 1/3 (minus jeden i jedna trzecia) + 6
5/12z = 4 2/3 (cztery i dwie trzecie) /:5/12
z= 56/5
z = 11,2
1 5 1
2010-03-24T16:54:17+01:00
1/4z + (z - 6) = 2/3 (z - 2)
1/4z + z - 6 = 2/3 z - 4/3
5/4z - 2/3z = 14/3
15/12z - 8/12z = 14/3
7/12z = 14/3 | : 7/12
z = 14/3 * 12/3
z = 8
1 5 1